Upgrading and development of computer automation and interface software for gas sensor measurement system - Wang, Tingting (2018)
With the continuous development of material science and the continuous advancement of microelectronics technology, the development of modern gas sensing field has grown for many years. In order to overcome the drawbacks and to achieve a better performance of semiconductor gas sensor under different experimental conditions, Gas Sensor Characterization System (GSCS), formerly known as Gas Sensor Measurement System is set up. Gas Sensor Characterization System is a computerized program which is developed to collect and record data from semiconductor gas sensors to be tested under a variety of experimental conditions. It established a flexible automated control system to achieve a group of different reasonable experimental environment for different applications and sensor products. The central computer is the control station of GSCS system with a fully functional and user-friendly interface to handle the measurement instruments. The measurement instruments are set up to obtain data from a gas sensor and provided a variety of experimental conditions such as temperature, humidity, voltage, current, the concentration of reducing gas and more. This measurement system was first built in 1995, and after that, the software system had undergone various of modification, upgrade, and implementation over the years by different FYP students in 1998, 2005 and 2009. The scope of this FYP in 2018 is to upgrade the software system to the latest operating system and software application which includes the replacement of physical connection between measurement instruments and central control station, the refactoring of the encrypted programming structures with minimal changing the external behaviors, the optimization and simplification of the current system.